Relationship between dimensions of employee burnout and employee satisfaction / Muhammad Fadli Abdul Fatah - Abdul Fatah, Muhammad Fadli (Faculty of Business and Management, 2017)
Past studies indicated that burnout in workplace among employees has been toone of the element in study is related to employee satisfaction. Boonratana and Gharleghi (2015) stated that burnout is a situation experience by human service professionals who appear to be exhausted or up to a state of inability to perform their tasks effectively or sometimes to even care for their clients. Other than that, burnout also defined as a condition in which one loses all concerns, feeling towards the person one works with and comes to treat them as impersonal object (Maslach, 1976). The term founder of “burnout”, Freudenberger (1974), defined that burnout as a situation experience faced by human service professionals who appear to be bushed or up to a state of inability to perform their tasks effectively. Maslach (1976) described that burnout as a condition in which one loses all concerns, feeling towards the individual one works with and comes to treat them as anonymous objects. However, by the late 1980s, researchers and practitioners began to recognize that burnout occurred outside the human services which are managers, entrepreneurs, and white- and blue collar workers (Schaufeli, Leiter and Maslach, 2008).